Implementation of Active Learning Student Created Case Studies with Flip Chart to Increase Self Directed Biology Learning in XI IPA 4 Class of SMA Negeri 4 Surakarta in Academic Year 2009/2010 - Suci Kusuma Dewi; Slamet Santosa; Muzayyinah Muzayyinah (Universitas Sebelas Maret, 2013)
This research own the target to increase self directed learning the student in biological study with applying active learning of Student-Created Case Studies accompanied by Flip Chart in class of XI IPA 4 SMA Country 4 Surakarta of teaching year 2009/2010. This research represent the research of claas action (Classroom Action Research) consited of two cysle. Every cycle consisted of 4 phase taht is planning, acting, observing, and reflecting. Subject research is student of class XI IPA 4 SMA Contry 4 Surakarta of teaching year 2009/2010. Technique of data complier used cover the enquette, observation, and interview. Data analysis used in this research is technique analisyse consited of the data reduction, data presetation, an withdrawal of conclusion or verivication. Result of research indicate taht the applying active larning of Student-Created Case Studies accompanied by Flip Chart can improve the self directed learning the student in biologycal study. Make-up of self directed learning the visible student passing result of enquette and observation. Mean assess the performance percentase every indicator from self directed learning obsevation the student at pre cycle is 14,68%, cycle I equal to 41,57%, and cycle II equal to 77,73. Mean assess the performance percentase every indicator from self directed learning enquette the student at pre cycle equal to 74,40%, cycle I equal to 79,74%, and cycle II equal to 80,29%. Its conclusion that applying active larning of Student-Created Case Studies accompanied by Flip Chart can improve the self directed learning. Key Words: Student-Created Case Studies, Flip Chart, Self Directed Learning